Two New Species of Monstrillopsis Sars (Crustacea: Copepoda: Monstrilloida) from the White Sea and Norway, with Comments on M. dubia Scott - Suárez-Morales, E.; Ivanenko, V.N. (ARCTIC, 2004)
A new species of monstrilloid copepod, Monstrillopsis ferrarii n. sp., based on four adult female specimens collected in the White Sea, northern Russia, is described and illustrated. The new species is most closely related to M. dubia Scott from Scotland and the Mediterranean and M. dubia (sensu Sars, 1921) from Norwegian fjords. The latter is considered to represent a distinct species, described herein as M. dubioides n. sp. It differs from M. dubia in characters related to antennule length compared to body length, but mainly to the shape and relative size of the genital double somite and other urosomal somites. Records of M. dubia in Norway and off Lisbon are referable to M. dubioides n. sp. On the other hand, M. ferrarii n. sp. differs from M. dubia, M. dubioides, and the other species of the genus by a combination of characters, including 1) two rounded protuberances in the cephalic area, flanking the ocelli; 2) a wide zone of transverse cuticular striations encircling the cephalic area; 3) very long exopodal setae on the fifth legs, with no distal elongation of the exopodal lobe beyond the setal bases; 4) a relatively long genital double somite with the margins of the anterior half produced laterally; and 5) the nearly equal sizes of the anal somite and the preceding somite. It is considered that M. dubia and related forms represent a species complex with subtle morphological differences and a wide distribution. This is the first record of a species of Monstrillopsis in Russia and the sixth species of this order to be recorded in polar environments. On décrit et illustre une nouvelle espèce de copépode de la famille des monstrillidés, Monstrillopsis ferrarii n. sp., établie d'après quatre spécimens femelles adultes prélevés dans la mer Blanche (Russie septentrionale). Cette nouvelle espèce est très proche de M. dubia Scott qui vit au large de l'Écosse et en Méditerranée, et de M. dubia (sensu Sars, 1921) présente dans les fjords norvégiens. On considère que cette dernière représente une espèce distincte, ...